ANALISIS TINGKAT KERAWANAN DAN RESILIENSI MASYARAKAT TERHADAP LONGSORLAHAN DI KECAMATAN JATIYOSO KABUPATEN KARANGANYAR TAHUN 2020 - Sri Rahayu; Chatarina Muryani; Setya Nugraha (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2022)
This study aims to (1) the level of vulnerability to landslides in Jatiyoso District, Karanganyar Regency in 2020, (2) the level of community resilience to landslides in Jatiyoso District, Karanganyar Regency in 2020, and (3) disaster mitigation directions carried out on landslide vulnerability in Jatiyoso District, Karanganyar Regency. The data analysis technique used in this study was descriptive qualitative. The results of this study are (1) The level of landslide susceptibility in the Jatiyoso District into three classes of landslide susceptibility: low, medium, and high. (2) There are two levels of community resilience to landslides, namely, a moderate level of resilience (55.56% from Jatiyoso District) and high resilience level (44.44% from Jatiyoso District). (3) The direction of disaster mitigation consists of zone II (moderate vulnerability), the need for restrictions on settlements, evaluation of the suitability of agricultural land, and the need for evaluation paths to refugee places, and zone III (high vulnerability) there needs to be a prohibition on development and this area should be specially used for conservation.